Implementation Evaluation of the Mother‐Child Education Program Among Refugee and Other Vulnerable Communities in Lebanon. Issue 167 (11th September 2019) - Ponguta, Liliana Angelica; Issa, Ghassan; Aoudeh, Lara; Maalouf, Cosette; Nourallah, Sawsan; Khoshnood, Kaveh; Zonderman, Anna Leslie; Katsovich, Liliya; Moore, Christina; Salah, Rima; Al‐Soleiti, Majd; Britto, Pia Rebello; et al.
Abstract: Despite the knowledge that quality early childhood development programs, including those that target parental knowledge and behaviors, are essential for ameliorating the negative effects of early‐life adversity, robust analyses of their implementation and impact in highly vulnerable settings are scarce. To address this knowledge gap, we conducted a pilot wait‐list randomized controlled trial (RCT) to assess the impact and the process of implementing and evaluating the Mother‐Child Education Program (MOCEP) among refugee families and one low‐income community in Beirut, Lebanon. This paper focuses on the analysis of MOCEP's implementation (i.e., key enablers of and barriers to the application and evaluation of the program). Our analysis suggests that, despite multiple challenges, implementation and robust evaluations of early childhood parenting programs in fragile contexts are feasible and urgently needed. This study illustrates how implementation evaluations are a key component of RCTs and crucial to identifying strategies to optimize program uptake and maximize impact.